An Unusual Presentation of Segmental Arterial Mediolysis. Issue 12 (5th December 2022) - Karna, Rahul; Kaye, Dylan; Jagdish, Balaji; Johnston, Alexandra; Venkat, Divya
ABSTRACT: Segmental arterial mediolysis (SAM) is a rare nonatherosclerotic and noninflammatory disease that often affects medium to large-sized arteries. We report a case of SAM involving bilateral hepatic arteries in an elderly woman. Although her initial presentation mimicked vasculitis, the clinical course and imaging led to the diagnosis of SAM. She was treated with coil embolization and stenting of the involved hepatic vessel leading to dramatic clinical improvement. It should be differentiated from vasculitis because there is no role of steroids in the management of SAM.